Global, regional, and national progress in financial risk protection towards universal health coverage, 2000–2030. (November 2022) - Rahman, Md Mizanur; Jung, Jenny; Islam, Md Rashedul; Rahman, Md Mahfuzur; Nakamura, Ryota; Akter, Shamima; Sato, Motohiro
Abstract: Introduction: Complete (100%) protection against catastrophic health expenditure (CHE) and impoverishment is the main target of universal health coverage (UHC). Evidence-based estimates must be at the heart of policy development for UHC, further research using updated data is essential to monitor, track, and compare country progress up to 2030. We estimate global, regional, and country-level CHE and impoverishment during 2000–2030. Methods: We aggregated 636 data points from 140 countries that were conducted between 2000 and 2021. We used Bayesian hierarchical model for trend and projection analysis. Furthermore, we constructed scenario-based projections of CHE and impoverishment based on 5% GDP spending on health and per capita health expenditure (PCHE) of 86. Results: Most countries fail to achieve financial protection targets by 2030, with the global incidence of CHE predicted to persist around 7% at 10% threshold. CHE is predicted to increase in most of Asia (Southern: 8.1% in 2000 to 13.4% in 2030; Central: 3.6%–23.2%; Eastern: 8.3%–14.4%; and Western: 7.3%–20.2%), Northern Africa (12.4%–27.2%), Eastern (7.1%–14.9%) and Northern Europe (6.6%–13.2%). In contrast, a decrease is predicted in Oceania, Latin America and the Caribbean, and Northern America. By 2030, incidence of impoverishment is predicted to be 0% worldwide at 3.10 poverty line, however in several African and Soth Asian countries is predicted to be high impoverishment. The scenario-based analysis indicated that CHE and impoverishment is expected to decrease in 41 and 42 countries for GDP increase and 43 and 62 for PCHE increase respectively compared to current spending on health. Conclusion: To accelerate progress towards reducing financial protection, governments should carefully assess the country context to determine how health can be prioritised through government spending to reduce out-of-pocket payments. Highlights: Globally, incidence of CHE remains virtually unchanged (7%) and impoverishment close 0·01% by 2030. Oceania, northern and Latin America seeing a decline in CHE but everywhere else increasing. Wide urban-rural disparity with high CHE found in most of Asian and African countries. Additional investment on health can significantly decrease the burden of healthcare expenditure.